Peak career in world-ranked swimmers: Age's analysis of 2008 Beijing Olympic Games participants - Tiago M. Barbosa; Mário J. Costa; Erik Mejias; Daniel A. Marinho; Hugo Louro; António J. Silva (Desafio Singular, 2013)
The aim of this paper was to: (i) describe the Beijing 2008 Olympic Games swimmer's ages and; (ii) compare ages according to swimmer's gender. It was analyzed 1101 inscriptions (588 men and 513 women) for all swimming events held at the Beijing 2008 Olympic Games: 50 meters freestyle (L50), 100 meters freestyle (L100), 200 meters freestyle (L200), 400 meters freestyle (L400), 800 meters freestyle (L800, only women) 1500 meters freestyle (L1500, only men), 100 meters backstroke (C100), 200 meters backstroke (C200), 100 meters breaststroke (B100), 200 meters breaststroke (B200), 100 meters butterfly (M100), 200 meters butterfly (M200). The final result lists was consulted at the Beijing 2008 Olympic Games official internet site, collecting the swimmer's name and chronological age for each event. Afterwards, chronological age was converted into decimal age at the day of the event heats. From the quartile analysis became clear that there was a tendency for the age median and variance to decrease from the shorter to the longest events for both genders. There were significant variations in the age, according to gender at the L400 ( p = .01), L1500/L800 ( p = .02), C100 ( p < .01), C200 ( p < .01), B100 ( p = .02), B200 ( p = .04), M100 ( p = .05) and M200 ( p < .01). For all these events, decimal age was higher for men than for women.